Physico-Chemical model and computer simulations of silicon nanowire growth - Efremov, A.; Klimovskaya, A.; Kamins, T.; Shanina, B.; Grygoryev, K .; Lukyanets, S . (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
A model of catalytically enhanced CVD growth of a silicon nanowire assembly on a substrate is developed, and growth process is simulated. Thermodynamic-kinetic theory is used for modeling of molecular transport in the gas phase, processes near catalyst surface and nanowire side of variable curvature, bulk diffusion of silicon adatoms through catalyst – body, and 2D nucleation. The simulation of atomic transport across surfaces is based on a long-wave approach of lattice gas approximation. To determine a character of atomic transport in TiSi₂-catalyst that is of great importance for application in Si-based technology, a density functional theory is used. The main result of modeling is that it is found a relationship between growth conditions (an initial radius of catalyst particles, their density, substrate temperature, content, pressure of gas, as well as properties of materials used) and, on the other hand, a growth rate, shape, composition, and type of atomic structure (amorphous or crystalline) of the nanowires grown. Besides, available experimental data published previously are discussed, and a qualitative agreement between theory and various experiments is obtained. This agreement gives rise to use the found relationship for controlling the nanowire growth.